Dampak Ubud Food Festival Terhadap Aspek Sosial dan Ekonomi Masyarakat di Banjar Penestanan Kaja, Ubud, Bali - Desak Gede Chandra Widayanthi; Ida Bagus Putu Puja; Desak Putu Candra Dewi; I Nengah Wirata (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
Bali is one of the provinces in Indonesia that carry out festival activities in various regions. One of the regular festivals held annually since 2015 is the Ubud Food Festival which is held in Banjar Penestanan Kaja, Ubud District, Gianyar Regency, Bali, Indonesia. Ubud Food Festival is a culinary festival featuring various Indonesian specialties. This research focuses on the social and economic impacts caused by the organizers of the Ubud Food Festival in Banjar Penestanan Kaja Ubud, Gianyar Bali, and expected to be useful for the organizers and the local community of Banjar Penestanan Kaja to find out all kinds of economic and social changes resulting from the implementation of the Ubud Food Festival which has been held for the past five years. Based on the results, it can be concluded that the implementation of an activity or event, has impacted the social and economic aspects for the community. Banjar Penestanan Kaja community, both positive and negative impacts.